The Electronic Procurement Initiation And Adoption In The Construction Industry - Yusuf Gedi, Sharif (2012)
This research aims to identify the essential factors that affect the initiation and the adoption of electronic procurement (EP) in the Malaysian construction industry. A mixed-methods sequential explanatory study was used to identify these factors in four different construction groups, namely, client, contractor, consultant, and supplier groups. In the quantitative study, the research focused on identifying the essential factors that affect the initiation and the adoption of EP in the Malaysian construction industry. Exploratory factor analysis (EFA) was used to identify these factors, which were grouped according to relatedness.